Gambaran Minat Belajar Mahasiswa Keperawatan Pada Pembelajaran Luring Pasca Pandemi Covid-19 - D’amorina Widi Ariawan, Meirachel; Permina, Yullya; Sudarta, I Wayan; Melati, Nimsi (STIKES Ngesti Waluyo, 2024)
The transition from online to offline learning makes students have to adapt again, causing student interest in learning to decrease. An initial study of 10 students found more interest in online learning because they could do many activities compared to offline, which had many obstacles. The purpose of this study is to determine the nursing students' interest in offline learning after the COVID-19 pandemic at STIKES Bethesda Yakkum Yogyakarta in 2024. The research method is qualitative descriptive, which is collected data from deep interviews. Data analysis techniques were transcribing, coding, categorizing, and using themes and source triangulation methods. The student population of the Undergraduate Nursing Study Program level III class of 2021 is 61 students with purposive sampling, a sample of 7 students. The results of the research from the interviews obtained 26 codes and 6 themes: 1) Learning impact, 2) Overcoming learning boredom, 3) Learning motivation, 4) Learning obstacles, 5) Classroom organization, and 6) Learning process. This study concludes that students are more interested in offline learning method because the material is easier to understand, and they can directly interact with lecturers and friends.